Supplement B to Working Bibliography of Chippewa/Ojibwa/Anishinabe and Selected Related Works (with Index) - Roufs, Timothy G (University of Minnesota, Duluth, 1988)
The "Working Bibliography of Chippewa/Ojibwa/Anishinabe and Selected Related Works" can be found by clicking the link under "Related to" in this record.